197k views
2 votes
add and express your answer in standard form (2x to the 4th +x to the third -4x squared +3) +(4x to the 4th -2x to the third-x squared +10x+2)

User Zut
by
5.6k points

1 Answer

4 votes

Answer:


\large\boxed{(2x^4+x^3-4x^2+3)+(4x^4-2x^3-x^2+10x+2)=6x^4-x^3-5x^2+10x+5}

Explanation:


(2x^4+x^3-4x^2+3)+(4x^4-2x^3-x^2+10x+2)\\\\=2x^4+x^3-4x^2+3+4x^4-2x^3-x^2+10x+2\qquad\text{combine like terms}\\\\=(2x^4+4x^4)+(x^3-2x^3)+(-4x^2-x^2)+10x+(3+2)\\\\=6x^4-x^3-5x^2+10x+5

User Xiaofan
by
6.0k points